PERSEPSI MASYARAKAT TENTANG PERKAWINAN SASUKU DI NAGARI AIR DINGIN KECAMATAN LEMBAH GUMANTI KABUPATEN SOLOK - Yurnelis, Yurnelis; Arifin, Zainal; Anggreta, Dian Kurnia (Pendidikan Sosiologi, 2013)
This thesis explain about society opinion of those doing the Marriage Sasuku in Nagari Air Dingin at Lembah Gumanti district at Solok regency who see couples daily life that having marriage sasuku and society perception of the couples that doing marriage sasuku. This study aimed to describe society views about marriage sasuku in Nagari Air Dingin at Lembah Gumanti district at Solok regency and describe the sanctions if the marriage sasuku had happened at Nagari Air Dingin society at Lembah Gumanti district at Solok regency. In doing this research, the writer use a fenomenologi theory that according to Alfred Schurt. This research use qualitative research approach using descriptive research type. Informants in this research is using purposive sampling technique that on purpose where is selected samples based on certain characteristics that needed in this research . Data were collected through observations and interviews. Data analysis was carried out interactively.Based on the results of this research that can be concluded that the society perception of marriage sasuku in nagari air dingin that society has to consider that the couples who do that marriage sasuku is considered as a person who does not have the traditional, crazy people, there are same with animals, and those that are not expected polite. Also resulted in his family life on the verge of contention, and also they have deformed in their generation that cause of the same genetics. Sanctions or fines for people who are given to couples who have marriage sasuku in Nagari air dingin as expelled from their village, ostracized from society, and even in wearing fine with paying as to kill one head of cattle ( cow, goat, buffalo ) and invite the whole peope of village for a bite to eat. It has been a tradition since formerly in Nagari Air Dingin.